2014
DOI: 10.5897/err2014.1729
|View full text |Cite
|
Sign up to set email alerts
|

Assessing model data fit of unidimensional item response theory models in simulated data

Abstract: The pupose of this paper is to give an example of how to assess the model-data fit of unidimensinal IRT models in simulated data. Also, the present research aims to explain the importance of fit and the consequences of misfit by using simulated data sets. Responses of 1000 examinees to a dichotomously scoring 20 item test were simulated with 25 replications. Also, data were simulated to fit the 2-PL model. 4-step procedure has been used for model-data fit and BILOG was used as software. Results were discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The last test assumption was the parameter invariance assumption test that aims to prove the parameter invariance of items and participants' ability (Köse, 2014). The items parameter invariance test was conducted to determine the items characteristics consistency that answered by the different group of the students.…”
Section: Discussionmentioning
confidence: 99%
“…The last test assumption was the parameter invariance assumption test that aims to prove the parameter invariance of items and participants' ability (Köse, 2014). The items parameter invariance test was conducted to determine the items characteristics consistency that answered by the different group of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the 3PL model was used for the analysis. Kose(2014) found that in a 1-, 2-and 3-paramter for assessing model data fit, 2-PL model fitted significantly better than the 3-PL model when -2Log likelihood ratio X 2 was used. However, when Orlando and Thissen (2000) evaluated model-data fit from fixed format tests, the results indicated that the three parameter logistic models combined with the generalized partial credit model among various IRT model combinations led to the best fit to the given data sets.…”
Section: Resultsmentioning
confidence: 99%
“…They held that model misfit has dire consequences leading to violation of invariance property. Thus, Kose (2014) emphasized that the property of invariance of item and ability parameters is the main stay of IRT that distinguishes it from CTT. The invariance property of item and ability is not dependent on the examinees distribution and characteristics of set of test items.…”
Section: Introductionmentioning
confidence: 99%
“…When the data are fit to the incorrect IRT model, Type I error increased and became inflated as impact increased for both sample sizes. Therefore, choosing an appropriate IRT model for existing data is an important consideration (e.g., Bolt et al, 2014;Köse, 2014;Maydeu-Olivares, 2013) and, done well, can be arduous. In their chapter on the assessment of modeldata fit, Hambleton et al (1991) recommend a comprehensive set of procedures for assessing IRT model fit including checking model assumptions, parameter invariance, and model predictions.…”
Section: Recommendationsmentioning
confidence: 99%